The Effect of Live Streaming and Online Customer Reviews on Consumer Purchasing Decisions of Jennskin Products Shopee - Putri, Camelia; Simamora, Virgo; Pravitasari, Endyastuti (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to examine the influence of Live Streaming and Online Customer Reviews on purchase decisions of Jennskin products on Shopee. Using a quantitative approach, data were collected from 100 consumers in Jakarta through a structured questionnaire and analyzed with SmartPLS 3.0. The results show that Live Streaming has a positive and significant effect on purchase decisions, while Online Customer Reviews do not have a significant influence. The model's R² value of 0.601 indicates that 60.1% of the variation in purchase decisions is explained by the two variables. These findings highlight the importance of interactive and promotional features in Live Streaming and suggest the need for improved customer review strategies. Future research is recommended to include broader variables and demographics for deeper insights.